Understanding how peer, romantic and family relationships influence adolescent sexual and reproductive health decisions: an exploratory study in two schools in the Western Cape, South Africa - Marthinus, Arlene Judith (Stellenbosch : Stellenbosch University, 2024)
Thesis (MA)--Stellenbosch University, 2024.